2018
DOI: 10.1093/europace/euy215
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of sex differences in atrial fibrillation: role of hormones and differences in electrophysiology, structure, function, and remodelling

Abstract: Atrial fibrillation (AF) is the clinically most prevalent rhythm disorder with large impact on quality of life and increased risk for hospitalizations and mortality in both men and women. In recent years, knowledge regarding epidemiology, risk factors and patho-physiological mechanisms of AF has greatly increased. Sex differences have been identified in the prevalence, clinical presentation, associated comorbidities and therapy outcomes of AF. Although it is known that age-related prevalence of AF is lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 144 publications
(138 reference statements)
5
52
0
Order By: Relevance
“…Moreover, the peaked levels of 2hG and 3hG at range of 81~90 ages suggested that glucose loading duration was prolonged by aging. Interestingly, men had a higher 2hG than women did, which is consistent with the gender difference of AF incidence [33]. Previous study had shown excess LPS led to age-associated hyperglycemia by inducing mitochondrial dysfunction, cellular senescence and adipose tissue dysfunction [45].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the peaked levels of 2hG and 3hG at range of 81~90 ages suggested that glucose loading duration was prolonged by aging. Interestingly, men had a higher 2hG than women did, which is consistent with the gender difference of AF incidence [33]. Previous study had shown excess LPS led to age-associated hyperglycemia by inducing mitochondrial dysfunction, cellular senescence and adipose tissue dysfunction [45].…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the peak glucose levels ( Figure 6B) and 2hG levels (Additional File 1:FigureS6A) in responding to OGTT were also progressively higher with aging. Interestingly, 2hG levels rise with increasing ages in both sexes, reaching higher levels in the men than women with same age (Additional File 1:FigureS6B), which is consistent with the gender difference of AF incidence [33]. The similar trend of aging phenotype still exists in DM and NDM patients, but 2hG levels were always higher in DM than NDM (Additional File 1:FigureS6C).…”
Section: Lps and Excess Glucose Synergistically Enhanced Nlrp3-in Ammsupporting
confidence: 75%
“…According to a 2019 update article from the American Heart Association, almost one in three adult men have some type of cardiovascular disease (10). Women are known to suffer cardiac disease 10-20 years later than men, which supports the hypothesis that physiological estrogen levels confer cardioprotective effects (11)(12)(13)(14). In the past decades, the effect of sex-related steroid hormones on the cardiovascular system has been predominantly focused on estrogen actions, whereas research concerning the beneficial cardiac effects of androgens has been limited.…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, a better understanding of the modifiable biomarkers, including an altered thyroid status, and molecular factors, including autoantibodies, may provide us with a chance to prevent AF or to tailor the treatment to avoid harmful consequences. It is noteworthy that women have worse and often atypical symptoms, as well as a higher risk for stroke and death, associated with AF compared to the risk in men [61].…”
Section: A Short Overview On Afmentioning
confidence: 99%